Практикум по геодезии: учебное пособие для геодезических специальностей вузов - Баканова В. В. Валентина Васильевна; Карклин Я. Я. Ян Янович; Павлова Г. К. Галина Кузьминична; Черемисин М. С. Михаил Сергеевич (Москва, Недра, 1983)
Авт. указаны на обороте тит. л.